Application of Platelet-Rich Fibrin as Regeneration Assistant in Immediate Auototransplantation of Third Molar with Unformed Roots: Case Report and Review of Literature - Hamzah Alkofahi; Alaa Maghaireh; Mamoon Fnaish; Mohammad Jarrah; Mohammad Bataineh (Hindawi Limited, 2020)
Background. Autogenous Tooth Transplantation (ATT) is the surgical movement of a maturely or immaturely formed tooth from its original site to another extraction site or a surgically prepared socket in the same individual. The most important factor in the healing process after autotransplantation is the presence of intact and viable periodontal ligament cells, which have the ability to differentiate into osteoblasts and able to induce bone production. ATT can successfully replace removable dentures as a restoration option in a growing patient, while implants can be placed only after skeletal maturity is attained. Case Presentation. In this case, we presented an immediate ATT of the third molar with unformed roots to the extraction socket of the first molar with evidence of continued root formation after 2 years of follow-up. Conclusion. Platelet-Rich Fibrin (PRF) can induce sustainable and accelerated healing, and it can also induce the regeneration process of the periodontal tissues and pulpal formation. This process plays a key role in future root development and success rate.